Spinal Muscular Atrophy Type 3: A Case Report (Bangladesh Journal of Child Health, 2020)
Spinal muscular atrophy (SMA) type 3 is a relatively stable genetically determined chronic neuromuscular disorder caused by degeneration of motor neurons of spinal cord. Patients with type 3 SMA may gradually experience decline in muscle strength and motor function. However functional progression is difficult to document and mechanisms remain poorly understood. A five years old boy presented with proximal muscle weakness, generalized hypotonia, absent deep tendon reflexes and features of neuropathy and labeled as SMA type 3.Bangladesh J Child Health 2019; VOL 43 (3) :183-187